Interior of Mahanaleshwar Temple Matha - Temples of India Project Team (Jio Institute, 2024)
The Mahanaleshwar temple matha consists of a central open-air courtyard with colonnades on all sides on the ground floor and a row of cells for the ascetics to rest, meditate or reside in the southern part of the upper storey. The pillars surrounding the open courtyard on the ground floor have been reused from some earlier construction at the site. Michael Meister has suggested that the pillars have been reused form the ruinous Triple-shrine Templewhich is in front of the Mahanaleshwar Temple.